Experimental investigation into droplet impingement upon moving films using high speed video and thermal imaging - Mitchell, Antony J.; Simmons, Kathy; Hann, David B. (2015)
Aeroengine bearing chambers are geometrically complex, typically containing shafts, bearings, seals and stationary components. Oil is supplied for lubrication and cooling and so the chamber contains a highly rotating two-phase (oil/air) flow where the oil is typically present as droplets, ligaments, mist and films. These films may be thick or thin and film speed varies with chamber location. It is desirable to know a priori the outcome of a droplet-film impact event in terms of mass, momentum and energy transfer. There is a significant body of research on the interaction between droplets and static films. The experimental parameter space has been characterised on the basis of film thickness and impact parameter to predict the outcome of an impingement. The impingement of droplets on moving films has only begun to be investigated over the last decade and consequently models have not yet been developed and the parameter space has barely begun to be characterised. Within this paper results are presented from an experimental study in which water droplets of 3 mm and 3.8 mm at 20°C falling under the influence of gravity impinged onto water films flowing down an inclined plane. Film temperature was 30°C and film thicknesses were between 2.3 mm and 4.2 mm. High speed imaging was used to determine the impingement outcomes and cavity morphology. A high speed infrared camera was used to determine the extent of the thermally affected region and its temperature behaviour. We find that by using the resultant droplet velocity (combining droplet and film velocities) the film impingement outcomes can be characterised into regions very similar to those for static films. The data is presented as a function of splashing parameter and non-dimensional film thickness. It was observed that for these impacts on supercritical films (Fr > 1) there is less propensity for secondary droplet formation through jet breakup than on static and subcritical films (Fr < 1). Data was obtained for extent of the thermally affected region. It was found that the cooler droplet liquid spreads over the inside of the crater before heating up to film temperature. Development of crater shape and size was also studied and data compared to established models for droplet impact on deep static films. During the initial stages of an impact crater area increases similarly to that for static films although the crater shape itself is less similar and is asymmetrical due to the film motion.